High resolution allele frequency analysis of HLA-A, HLA-B, HLA-DRB1, HLA-C, HLA-DQB1 and HLA-DPB1 in Guangdong Cord Blood Bank - RUI Derong; ZOU Hairong; FENG Haoxin; ZHANG Jing; LUO Jiewen; GAO Zhaoxin (Zhongguo shuxue zazhi, 2024)
[Objective] To analyze the characteristics of HLA-A, HLA-B, HLA-DRB1, HLA-C, HLA-DQB1 and HLA-DPB1 allele polymorphisms among cord blood donors in Guangdong population. [Methods] According to HLA high resolution genotyping data of 32 717 samples of cord blood donors from Guangdong Cord Blood Bank from January 2009 to December 2023, the allele frequencies were calculated by direct counting and the haplotype frequencies were calculated by using Arlequin software 3.5.2.2. [Results] A total of 102 HLA-A alleles, 160 HLA-B alleles and 96 HLA-DRB1 alleles were detected in 32 717 samples. Among them, 46 HLA-DPB1 alleles were detected in 5 377 samples, and 66 HLA-C alleles and 35 HLA-DQB1 alleles were detected in 13 310 samples. The most common alleles were HLA-A*11∶01 (28.96%), HLA-B*40∶01 (15.23%), HLA-DRB1*09∶01 (15.72%), HLA-C*01∶02 (19.40%), HLA-DQB1*03∶01 (20.85%) and HLA-DPB1*05∶01 (40.79%). The most common 3 loci haplotype and 6 loci haplotype were HLA-A*02∶07-B*46∶01-DRB1*09∶01 (1.55%), HLA-C*07∶02-DQB1*03∶01-DPB1*05∶01 (1.77%), HLA-DRB1*09∶01-DQB1*03∶03-DPB1*05∶01 (3.31%) and HLA-A*02∶07-B*46∶01-C*01∶02-DRB1*09∶01-DQB1*03∶03-DPB1*05∶01 (0.30%). [Conclusion] In this study, the allele and haplotype frequencies of HLA-A, HLA-B, HLA-DRB1, HLA-C, HLA-DQB1 and HLA-DPB1 were obtained in the cord blood donors in Guangdong, which can provide important reference data for HLA gene related research and the selection of donors for clinical application.